TRANSITION FROM STATIC TO DYNAMIC FIELDS IN THE PRESENCE OF DYONS - Ömer Zor (Uludağ University Journal of The Faculty of Engineering, 2022)
We assumed the existence of dyons. Since the dyon is a particle with electric and magnetic charges, we simply considered that electric charge and corresponding magnetic charge have the same small velocity. Thus using this proposition and neglecting the interaction between electric and magnetic charges, we constructed symmetric microscopic Maxwell equations in the presence of dyons. Eventually we expanded the theory and obtained macroscopic Maxwell equations in vacuum using averaging process.